Determining the factors influencing indigenous youth become a successful entrepreneurs - Amiruddin, Mohd Hasril; Sumarti, Sri; Suib, Siti Normah; Ibrahim, Azhani Che; A. Jalil, Siti Afiat (GADING, 2020)
Eleventh Malaysia Plan, 2016-2020, focused more on macroeconomic policies, create more jobs and highly skilled human resources. The national development agenda also includes indigenous youth in Malaysia. Poverty was identified as the main challenge faced by the government in developing the indigenous community youth. To solve this problem, the government through the current economic plan is to focus attention on efforts to produce more entrepreneurs among indigenous youth in Malaysia. However, the number of indigenous youth entrepreneurs still low and most of the indigenous are still below the poverty line. Therefore, this study aims to determine the factors that influence indigenous youth to become successful entrepreneurs. This qualitative study participant were experts involved and directly related to indigenous entrepreneurship in Malaysia. Participants in this study were selected to use purposive sampling. The instrument of this study was the interview protocol, where the researcher provided only the main question, and the follow-up question was based on the interview participant's answer. The semi-structured interview data were analyzed using thematic analysis, by demarcating interview data, coding, finding themes, revising themes, defining and naming themes and generating reports. The study found that there are five main factors that influence indigenous youth to become successful entrepreneurs, among them are the demographic factors, suitable entrepreneurship and characteristics of entrepreneurs suitable for indigenous youth, transferable skills and policy and financial assistance to expand indigenous businesses. Therefore, it is expected that this study will provide guidance to the parties concerned to increase the number of successful entrepreneurs among indigenous youth in Malaysia.